2022
DOI: 10.21608/ejhm.2022.273067
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oral Activated Charcoal in decreasing Blood Urea, Creatinine and Phosphorous in Chronic Kidney Disease

Abstract: Background: In recent years, chronic kidney disease (CKD) has become a worldwide public health issue. Objective: The main aim of this study was to explore the ability of oral activated charcoal to adsorb uremic toxins limiting the progression of CKD and delaying the need for hemodialysis in patients with CKD stages III and IV and to compare its effect with the effect of dry seeds (lentils) as absorbents of uremic toxins. Patients and methods: A randomized controlled clinical trial was conducted on 90 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…A study by Al-Shazly et al . [ 25 ] showed similar results over a 12-week follow-up period, where the activated charcoal group had a significant decrease in serum urea and phosphorus compared to the control group. Another study by Gao et al .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A study by Al-Shazly et al . [ 25 ] showed similar results over a 12-week follow-up period, where the activated charcoal group had a significant decrease in serum urea and phosphorus compared to the control group. Another study by Gao et al .…”
Section: Discussionmentioning
confidence: 73%
“…The activated charcoal group showed a significant decrease in serum urea and phosphorus throughout the follow-up period. A study by Al-Shazly et al [25] showed similar results over a 12-week follow-up period, where the activated charcoal group had a significant decrease in serum urea and phosphorus compared to the control group. Another study by Gao et al [26] supported these findings, demonstrating that the phosphorus levels in the oral-activated charcoal group started to decline in the third month and remained lower than those in the placebo group throughout the experiment.…”
Section: Acknowledgmentsmentioning
confidence: 72%